IMPLEMENTASI MEDIA UTANGKLEK TERHADAP PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR - Frandika Fajar Juliarto; Ika Oktavianti; Imaniar Purbasari (PGSD Universitas Muria Kudus, 2020)
This study aims to describe the application of the traditional utangklek game and examine the improvement of student learning outcomes on the theme of 5 sub-themes of ecosystem balance class V SDN Widorokandang. Classroom action research was conducted in class V SDN Widorokandang Pati with 20 students as research subjects. This research consists of two cycles and each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The independent variable in this study is utangklek media. While the dependent variable is learning outcomes. The research instrument consisted of tests, observations, interviews, and documentation. The analysis used is qualitative analysis and quantitative analysis. The results showed there was an increase in completeness of the learning outcomes aspects of students' knowledge of social studies in the first cycle by 60% and the second cycle by 80%. The completeness of learning outcomes for Indonesian content in cycle I was 65% and cycle II was 80%. Learning outcomes aspects of social studies students' skills in the first cycle by 65% in good qualifications increased in the second cycle by 80% in good qualifications. The completeness of learning outcomes of Indonesian content in the aspect of skills in the first cycle by 55% in the qualifications is good enough to 80% in the good qualifications. It proves that the application of the traditional utangklek game can improve the learning outcomes of fifth grade students at SDN Widorokandang.